Airway closure in a patient with acute heart failure: a case report - Bien Huu-Thien Le; Minh Vu-Anh Phan; Khanh Bao Lieu; Yen Thi-Hai Hoang; Phuong Phan-Phuong Pham; Hau Huu-Doan (The Egyptian Heart Journal)
Abstract Background Airway closure occurs in small airways and disconnects distal airways from proximal airways. This pathology may lead to acute pulmonary edema, worsening gas exchange and creating challenges in ventilator management. Case presentation We report the case of a 68-year-old woman who was admitted to the hospital because of non-ST elevation acute myocardial infarction and was subsequently intubated because of refractory pulmonary edema. The low-flow inflation procedure revealed airway closure, and the positive end-expiratory pressure was titrated according to the airway opening pressure. Conclusions Acute pulmonary edema may be accompanied by airway closure. A simple bedside procedure can indicate the presence of this complication and guide positive end-expiratory pressure setting.